(untitled) (Bangladesh Journal of Neuroscience, 2016)
Primary craniocerebral plasmacytomas are uncommon and represent only 0.7 % of all plasmacytomas. In this case solitary plasmacytoma in the midline frontal head region of the skull and discuss the clinical features and prognosis of this tumor. Plasmacytoma can present as multiple myeloma, solitary plasmacytoma of the bone or extramedullary plasmacytoma. Solitary plasmacytoma is a rare entity that composes of malignant plasma cells and involves the bone to form only one or two lesions without evidence of disease dissemination. It accounts for only 4% of malignant plasma cell tumors. 50 years old male was suffering from plasmacytoma in the frontal head region in our case which is pulsatile. On images showed multiple differential diagnosis but after operation histological examination revealed plasmacytoma. Bangladesh Journal of Neuroscience 2016; Vol. 32 (1): 39-42